City of dragons - Hobb, Robin., Author (New York Harper Voyager, 2012)
Accompanied by human keepers, the dragons embark on a dangerous journey to their ancient, mythical homeland of Kelsingra, and along the way form deep bonds with the humans that are severely tested during the journey's final days.
Keywords: Dragons -- Fiction; Imaginary places -- Fiction; Quests (Expeditions) -- Fiction; Voyages and travels -- Fiction; Human-animal relationships -- Fiction; Magic -- Fiction; Animals, Mythical -- Fiction; Fantasy fiction; Science fiction